STUDY OF ATTITUDE AND PERCEPTION OF MEDICAL STUDENTS REGARDING THE MEDICAL CURRICULUM AND SYLLABUS IN A TEACHING MEDICAL COLLEGE OF EASTERN INDIA - Debasis, Bandyopadhyay (Journal of Drug Delivery and Therapeutics, 2013)
Background: Recently there is emphasize on better development of skill, behaviors, and attitudes of medical students, the future doctors, in all part of the world. For that well-constructed medical curriculum cum syllabus is essential. There is rapid change of disease pattern and change of social demand from the doctors, need the change of medical curriculum and syllabus. It necessitates the good planning of the change of curriculum and syllabus. Good feedback from the medical students regarding the attitude and perception of current curriculum and syllabus can only improve the quality of the planning and subsequent change. Lots of studies conducted on this area in different part of the world, yielding varying results. In this perspective there was need for further studies, especially in this part of the world, Burdwan Medical College, West Bengal, India, where there was no such studies conducted before.Objective: The objective of my study was to assess the attitude and perception of the medical students regarding the present medical curriculum and syllabus with emphasis on the gender difference if any. Materials and Methods: Pre validated, Reliable, standardized, predesigned 11 points based structured questionnaires were distributed among randomly recruited 90 medical students of final M.B.B.S. of 2007-2008 batch, during the 3rd week of the January 2012. The response of the questionnaires was assessed in the five point Likert scale.Results: Out of the 93.33% responder, male was 91.379% & female was 96.875%. 73.56% female students & 78.50% male students disagreed, including strongly disagreed that their problem solving skill were being developed by this syllabus. 73.58% of female students & 81.48% of male students disagreed, including strongly disagreed that the enjoyment outweighs the stress of the syllabus. Whereas more than 80% of both female & male students agreed, including strongly agreed regarding the adequacy of the current time span within the syllabus. But more than 87% of both male & female students agreed, including strongly agreed regarding the need of change of medical curriculum & syllabus, with more focused towards on the problem based learning ( PBL). Conclusion: Though the study conducted in one institution & in one academic year, but majority of the both male and female medical students of this institution gave their favoring opinion regarding the change of medical curriculum& syllabus, focused more on PBL. Key words: Medical, Curriculum, Syllabus, Attitude, Perception. Â